2019
DOI: 10.1002/ccd.28398
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of alternative access for cardiac catheterization and percutaneous coronary intervention: Dorsal distal radial and ulnar artery catheterization

Abstract: The femoral and radial arteries are the standard access routes for cardiac catheterization. In cases where the right radial artery has been previously utilized or is not suitable for repeat procedures, the left dorsal distal radial artery (anatomical snuff box) or the ulnar artery may be an alternative access site. In this systematic review, alternative access sites are described along with the techniques of cannulation, technical considerations, ultrasound imaging, clinical studies, and their complications. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Transradial access (TRA), which is characterized by a low incidence of complications, such as radial artery occlusion, hematoma, spasm, etc, 1 is currently considered as the default choice in cardiac catheterization Distal radial access (dTRA), also called “snuff box” access, has gain increased interest in the field of interventional cardiology due the low incidence of complications as well as for the comfort offered to both the patient and the operator. 2,3 This increased interest in this novel vascular access has led to the publication of several reports increasing the available data on this issue, However, a comprehensive and updated comparison between conventional (cTRA) and dTRA is lacking. 4 Aim of the present study is to provide an updated comparison of the complications between dTRA and cTRA access after coronary angiography and/or PCI performing a systematic review and meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Transradial access (TRA), which is characterized by a low incidence of complications, such as radial artery occlusion, hematoma, spasm, etc, 1 is currently considered as the default choice in cardiac catheterization Distal radial access (dTRA), also called “snuff box” access, has gain increased interest in the field of interventional cardiology due the low incidence of complications as well as for the comfort offered to both the patient and the operator. 2,3 This increased interest in this novel vascular access has led to the publication of several reports increasing the available data on this issue, However, a comprehensive and updated comparison between conventional (cTRA) and dTRA is lacking. 4 Aim of the present study is to provide an updated comparison of the complications between dTRA and cTRA access after coronary angiography and/or PCI performing a systematic review and meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…They suggest that use of the dorsal distal radial artery, avoiding the volar forearm compartment, may reduce the risk of compartment syndrome in the setting of postprocedural hematoma formation. 12 Data on the safety of ipsilateral transulnar access in the setting of radial artery occlusion or previous transradial access are limited, and published guidelines do not recommend it at this time. 10 Despite that, a recent survey conducted by the American College of Cardiology Foundation found that 3% of cardiologists listed ipsilateral (described as homolateral) transulnar access as their preferred access site following failed transradial access attempt.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of the transulnar approach are explained by the deeper path in the forearm, making palpation more difficult and the most laborious hemostasis as a result of the absence of compression under a rigid surface such as bone structure (28,29). Local complications can be the same through the radial approach, associating the ulnar nerve injury.…”
Section: Limitations Of the Ulnar Accessmentioning
confidence: 99%